The Influence Of Task and Personality Characteristics On Employee Turnover and Absenteeism Incidents - Mowday, Richard T.; Spencer, Daniel G. (Academy of Management Journal, 1981)
The article presents a study which examined the influence of task and personality characteristics on employee turnover and absenteeism incidents. The subjects of the study were 569 employees working in 7 state and county government agencies in a midwestern state. The analysis was designed to measure employees perceptions of their task characteristics using a 14-item short-form of the Job Diagnostic Survey. The analysis also gathered information on turnover and absenteeism rates. Regression analysis was used to analyze the data gathered. The results showed that perceived job scope is related to both turnover and absenteeism.